Development and Clinical Translation of Approved Gene Therapy Products for Genetic Disorders - Shahryari, Alireza; Saghaeian Jazi, Marie; Mohammadi, Saeed; Razavi Nikoo, Hadi; Nazari, Zahra; Hosseini, Elaheh Sadat; Burtscher, Ingo; Mowla, Seyed Javad; Lickert, Heiko (Frontiers in Genetics, 2019)
The field of gene therapy is striving more than ever to define a path to the clinic and the market. Twenty gene therapy products have already been approved and over two thousand human gene therapy clinical trials have been reported world-wide. These advances raise great hope to treat devastating rare and inherited diseases as well as intractable illnesses. Gene therapy is presently starting to become commercially profitable as a number of gene and cell-based gene therapy products have been approved and have entered the market and the clinic. Understanding the precise pathomechanisms of diseases as well as emerging efficient and specific gene targeting and delivery tools are revolutionizing the global market. Currently, human cancers and monogenic disorders are indications number one. The elevated prevalence of genetic disorders and cancers, clear gene manipulation guidelines, as well as increasing financial support for gene therapy in clinical trials are major trends. This article addresses the history and development of twenty approved human gene and cell-based gene therapy products that have been approved up-to-now in clinic and markets of mainly North America, Europe and Asia.